STRATEGI MENGATASI DAMPAK DIGISEKSUAL TERHADAP KEHARMONISAN KELUARGA MUSLIM DI ERA SOCIETY 5.0 PERSPEKTIF MAQASHID SYARIAH - Adlin, Arief Budiman; Husaini, Akhmad (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Digisexuality defined as a sexual inclination reliant on technologies such as artificialintelligence (AI), virtual reality (VR), and sex robots, has become a significant challenge to the integrity of Muslim households in the era of Society 5.0. This phenomenon disruptsmarital relationships on psychological, spiritual, social, and moral levels. This study aims to examine the impact of digisexuality on family harmony and to formulate counter-strategies based on the perspective of Maqasid Sharia. Using a qualitative approach and library research method, the study draws upon primary and secondary sources including Islamic jurisprudence, tafsir, academic journals, and relevant digital data. The findings reveal that digisexuality negatively affects five core objectives of Maqasid Sharia: religion, intellect, honor, lineage, and wealth. In response, five integrative strategies are proposed: (1) Islamic sexual ethics ; (2) Islamic sexual education based on digital media; (3) managing media communication and digital financial technology; (4) increasing quality time through digital literacy within the household; and (5) revitalizing religious education in the domestic sphere. These strategies are curative, preventive, and transformative in strengthening the moral and spiritual resilience of Muslim families amid the growing wave of digitalization. ABSTRAK Digiseksualitas yaitu kecenderungan seksual yang bergantung pada teknologi seperti AI,VR, dan robot seks, telah menjadi tantangan nyata dalam menjaga keutuhan keluarga muslim di era Society 5.0. Fenomena ini mengganggu relasi suami istri secara psikologis, spiritual, sosial, dan moral. Penelitian ini bertujuan untuk mengkaji dampak digiseksualitas terhadap keharmonisan keluarga serta merumuskan strategi penanggulangannya berdasarkan perspektif Maqashid Syariah. Penelitian menggunakan pendekatan kualitatif dengan metode studi pustaka, memanfaatkan sumber-sumber primer dan sekunder seperti buku fikih, tafsir, jurnal ilmiah, dan data digital relevan. Hasil kajian menunjukkan bahwa digiseksualitas berdampak pada lima aspek utama maqashid syariah: agama, akal, kehormatan, keturunan, dan harta. Sebagai respons, dirumuskan lima strategi integratif: (1) Etika seksualitas dalam islam ; (2) Edukasi seksual islam berbasis media digital (3) Mengelola Media Komunikasi dan Teknologi Finansial Digital (4) Peningkatan quality time dengan literasi digital dalam keluarga (5) Revitalisasi pendidikan agama dalam lini keluarga. Kelima strategi tersebut bersifat kuratif, preventif, dan transformatif dalam membangun ketahanan nilai dan spiritualitas keluarga muslim di tengah arus digitalisasi yang terus berkembang.